Using A Subsurface Vertical Flow System to Remediate Municipal Wastewater - Karaghool, Haneen A. Kh.; N. Ismaeal, Nizar (International Journal of Sustainable Construction Engineering and Technology, 2022)
The goal of this study is to determine the efficacy of plants in the treatment of municipal wastewater (MWW) utilizing the aquatic plant common reed, also known as Phragmites australis. Two glass basins with dimensions of (60 cm x 26 cm) and a height of (60 cm x 26 cm) have been developed for this purpose (30 cm). In this investigation, two basins were employed: one served as a reference, while the other was used to conduct tests using synthetic and actual city wastewater. The plant treatment basins with vertical subsurface flow (VSSF) system was used in this investigation because it provides greater ventilation. Furthermore, the retention duration is many hours due to water molecules penetrating the basin's layers of packing materials, which have a rather high hydraulic conductivity. Three layers of aggregates, sand, and agricultural sand were used to cover the basins' bases: the first layer was 3 cm of aggregates, the second was 3 cm of sand, and the final layer was 4 cm of agricultural sand. Before beginning the experiment, the plants were acclimated for two weeks. To imitate municipal wastewater, lab-created synthetic wastewater was employed. Samples were collected and tests were performed after four weeks of running the trials to determine certain significant pollution indicators and their elimination percentage. TDS= 20.6 %, TSS= 65 %, BOD5=75 percent, COD=64.1 %, and TH= 47.2 % were the findings. The capacity of Phragmites australis to function as a biofilter in the treatment process was demonstrated by its use in the phytoremediation of municipal wastewater.